Identification Bioactive Compound of Ethanol-Water Fraction of Coleus atropurpureus for Anti-rheumatic Rheumatism in CFA-induced Rats - Ipang Djunarko; Nanang Fakhrudin; Arief Nurrochmad; Subagus Wahyuono (Sanata Dharma University, 2022)
Nonsteroidal anti-inflammatory drugs are used for pain and to slow the progression of rheumatoid arthritis. Accordingly, the discovery of rheumatoid arthritis active compounds from the ethanol-water fraction Coleus atropurpureus (EWC) was conducted to characterize the isolated compounds as well as the anti-rheumatic effects of the EWC induced Complete Freund's Adjuvant (CFA). We conducted in vivo study in rats which were randomly divided into 5 groups. Group 1 was only given CFA as a negative control. Group 2 as positive control was orally exposed to diclofenac potassium (9 mg/BW). Three groups were given different EWCs orally as follows: 11.25 mg/BW, 22.5 mg/BW, and 45 mg/BW, respectively. Rheumatism rates were then compared with positive controls using a visual arthritic scoring system. The compounds identified by isolation of the EWC of Coleus atropurpureus predicted forskolin. The ethanol-water fraction Coleus atropurpureus did not act as an anti-rheumatic arthritis agent in CFA-induced rats.